2003
DOI: 10.1002/ana.10465
|View full text |Cite
|
Sign up to set email alerts
|

μ Opioid receptors and analgesia at the site of a peripheral nerve injury

Abstract: Opioid ligands may exert antinociception through receptors expressed on peripheral afferent axons. Whether local opioid receptors might attenuate neuropathic pain is uncertain. In this work, we examined the function and expression of local mu opioid receptors (MORs) associated with the chronic constriction injury (CCI) model of sciatic neuropathic pain in rats. Low-dose morphine or its carrier were percutaneously superfused over the CCI site with the injector blinded to the identity of the injectate. Morphine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
87
2
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 53 publications
8
87
2
7
Order By: Relevance
“…Similar effects were observed after PSL (Rashid et al, 2004;Pol et al, 2006), although -receptor immunoreactivity (analyzed by Western blot) was enhanced in another study (Walczak et al, 2005). After CCI, there was no strict correlation between -receptor mRNA and protein levels, in that mRNA was unchanged (Truong et al, 2003) or down-regulated (Obara et al, 2009(Obara et al, , 2010, whereas the number of -receptor-expressing neurons was enhanced (Truong et al, 2003) or unaltered (Kolesnikov et al, 2007). In the same model, a reduction (by 37-39%) of the stimulation of G protein coupling to -receptors by morphine, but not by endomorphins, was reported (Obara et al, 2010).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Similar effects were observed after PSL (Rashid et al, 2004;Pol et al, 2006), although -receptor immunoreactivity (analyzed by Western blot) was enhanced in another study (Walczak et al, 2005). After CCI, there was no strict correlation between -receptor mRNA and protein levels, in that mRNA was unchanged (Truong et al, 2003) or down-regulated (Obara et al, 2009(Obara et al, , 2010, whereas the number of -receptor-expressing neurons was enhanced (Truong et al, 2003) or unaltered (Kolesnikov et al, 2007). In the same model, a reduction (by 37-39%) of the stimulation of G protein coupling to -receptors by morphine, but not by endomorphins, was reported (Obara et al, 2010).…”
supporting
confidence: 62%
“…All three opioid receptors were detected using immunohistochemistry in PERIPHERAL PAIN INHIBITION sensory fibers coexpressing CGRP at the CCI site of the sciatic nerve trunk . Furthermore, an up-regulation of -and ␦-receptors was detected by Western blot at the nerve injury site (Truong et al, 2003;Kabli and Cahill, 2007), and enhanced -receptor-immunoreactivity was found in hindpaw skin innervated by the damaged saphenous nerve after PSL or CCI (Walczak et al, 2005(Walczak et al, , 2006. All these alterations were demonstrated 1 to 14 days after nerve injury.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Although it has been suggested that neuropathic pain may be attenuated by opioids at higher doses than those effective in acute pain [11], this is accompanied by aggravation of central side effects and studies show that even neuropathic pain patients that acknowledge medical benefit with opioids drop out of therapy within months due to such side effects [12]. Although recent studies have demonstrated local administration of μ-opioid agonists reduced mechanical allodynia in models of rat neuropathic pain [13][14][15][16], possible beneficial effects of systemically administered opioids which are peripherally restricted have not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Isso corrobora STEIN (1993) e ANTONIJEVIC et al (1995 que inferem que a ação antinociceptiva dos agonistas opioides é pronunciada no tecido infl amado, mas pouco evidente em tecidos íntegros em diversas espécies animais. O sistema opioidérgico é efi ciente para modular a resposta nociceptiva no tecido infl amado (TRUONG et al, 2003) conforme a natureza do estímulo e o estágio da reação infl amatória tecidual (MILLAN, 1986) que podem ativar os receptores opioides periféricos (STEIN & LANG, 2009). Também nos tecidos periféricos é necessário haver infl amação tecidual para que a morfi na promova adequado efeito analgésico (LIKAR et al, 2001).…”
Section: Resultsunclassified